The peach meadow orchard system. IX. Yield of cultivars during ten years on biennial drastic pruning - Barbosa, Wilson; Orto, Fernando Antonio Campo Dall; Ojima, Mário; Santos, Rui Ribeiro dos; Kalil, Geovanita Paulino da Costa; Fahl, Joel Irineu; Carelli, Maria Luiza Carvalho (Pesquisa Agropecuaria Brasileira, 1999)
Fourteen peach (Prunus persica L. Batsch) and nectarine cultivars and selections, budded on Okinawa rootstock, were grown under the meadow orchard system, with biennial drastic pruning at 4 x 1.5 m spacing. Results obtained during ten years of experiments (1986-95) clearly indicate that 'Aurora-1', IAC 680-178, IAC 680-13, 'Talismã', 'Régis' and 'Flordaprince' peaches were the best, with an average yield (fruits) per tree of 112, 9.2; 94, 8.5; 95, 8.1; 99, 8.1; 98, 7.8 and 91,7.7 number and kg/tree respectively. The biennial drastic pruning decreased the yield of trees every two years, without affecting the average decennial productivity. In 1995, data on trunk cross-sectional area, fruits and mass per cm2 of trunk and leaf area presented significant differences among cultivars and selections.